PELESTARIAN BATIK SEBAGAI IDENTITAS NASIONAL DI ERA DIGITAL - Alivia Salsabila Herlina Sari; Siti Hamidah; Rifa’atussalwa Hayati; Sonya Trikandi (STKIP Subang, 2026)
Batik is an Indonesian cultural heritage that plays a crucial role as a national identity. In the digital era, the preservation of batik faces new dynamics shaped by technological advancement, cultural globalization, and changes in public consumption patterns. This article aims to analyze the preservation of batik as a national identity in the digital era by examining its opportunities, challenges, and preservation strategies. This study employs a descriptive qualitative method through literature review of academic books, national and international journals, and official documents related to batik and culture. The findings indicate that the digital era provides significant opportunities for batik promotion and innovation through social media and digital platforms; however, it also presents challenges such as excessive commercialization, cultural value shifts, and declining understanding of batik’s philosophical meanings among younger generations. Therefore, adaptive and sustainable preservation efforts are required through cultural literacy enhancement, wise utilization of digital technology, and strong government policy support alongside youth participation to maintain batik as Indonesia’s national identity. Keywords: Batik, national identity, cultural preservation, digital era.